Results of Archaeological Research in the Acropolis of Falasarna, Crete - Greek Ministry of Culture and Sports (Les Carnets de l’ACoSt)
Finds mainly from the Archaic period were brought to light by the excavation of the central area of the ancient temple of Demeter in the acropolis of Falasarna in Crete. Among the finds was an abundance of terracotta figurines.